2003
DOI: 10.1046/j.1365-2796.2003.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coronary heart disease: a comparison between the Copenhagen risk score and the Framingham risk score applied to a Dutch population

Abstract: Results. The average 10-year risk for CHD was significantly different between the FRS (4.6%, SD 5.0) and the CRS (3.2%, SD 4.1). The correlation between the two estimates was 0.94 (P < 0.001). The Bland-Altman figure shows a large proportion of agreement, but with an increasing difference with increasing average risk. When examining the separate risk factors age, total cholesterol, HDL cholesterol and systolic blood pressure and smoking, there appear differences between the two risk functions. Conclusion. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…It should be noted that the applied Framingham equation is known to overpredict in European populations [23,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the applied Framingham equation is known to overpredict in European populations [23,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The Framingham equation was chosen for comparison, as it is probably the most widely used and quoted conventional cardiovascular risk equation. There are also data to suggest that other conventional risk equations, whereas they may be better calibrated to certain populations, tend to order patient risk estimates similarly (in non-HIV-infected populations) [23,24]. The formulation of the Framingham equation derived by Anderson et al [22] was chosen as this allowed most direct comparison with the endpoints collected in the DAD Study, and also allowed reasonably straightforward computations.…”
Section: Comparison With Standard Cardiovascular Risk Equationsmentioning
confidence: 99%
“…Danish and Dutch populations [21,22], as well as Japanese American and Hispanic men [23]. More recently, another report indicated similar overestimation of the original Framingham functions for CHD in the Chinese Multiprovincial Cohort study (CMCS); for example, in the 10th decile in men, the predicted rate was 20% vs. an actual rate of only 3% [24].…”
Section: Performance Of Caucasian-derived Decision Rulesmentioning
confidence: 91%
“…Further, it has been reported that the Framingham risk model is not applicable in different populations. 24,25 Thus, the MEGA risk score might be superior in its accuracy for determining CHD risk in patients with moderate hypercholesterolemia, such as Japanese patients.…”
Section: Discussionmentioning
confidence: 99%